E-GOVERNMENT SEBAGAI BENTUK BARU DALAM PELAYANAN PUBLIK: SEBUAH TINJAUAN TEORITIK - Bambang Irawan (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The fundamental spirit in electronic government is all about giving the best service for public interests. It is a way for government to use the new technologies to provide people with more convenient access to government information and services, to improve the quality of the services and to provide greater opportunities for the people to participate significantly in policy making process. Electronic government is also the use of information and communications technology to promote more efficiency and cost-effective government, then allow greater public access to informations, and make government more accountable to citizens. This article is a theoretical study about electronic government as the new model of public service.